CONSTRUCTING SUSTAINABLE ECONOMY FOR MICRO-SIZED ENTERPRISES THROUGH QARDHUL HASSAN FINANCING BASED ON ISLAMIC PHILANTHROPY FUNDS - Santo Hartono, Haryani (Program Studi Manajemen Zakat dan Wakaf, 2024)
The research aims to describe the role of halal financing based on Islamic philanthropy funds in building up economy for micro scale enterprises. This research was conducted on BANKZAKAT (Indonesian: Bantuan Keuangan Berbasis Zakat), a financial aid institution based on zakat, infaq, and sadaqah funds which is a program of BAZNAS Musi Rawas Regency. This study uses a descriptive qualitative research method. Data obtained by means of observation and interviews. The results show that qardhul hassan financing based on Islamic philanthropy funds provides the potential for poverty alleviation, releases from the trap of moneylending with multiple interest rates, and raises awareness to participate in continuing kindness to others by raising the level of life from mustahik to first become munfiq and being potential muzakki. Qardhul hassan financing is a solution in constructing economic sustainability, especially for micro and super micro enterprises.